Importance of sand particle size and temperature for nesting success of green turtles in Penang Island, Malaysia - Mohd Salleh, Sarahaizad; Nishizawa, Hideaki; Ishihara, Takashi; Mohd Sah, Shahrul Anuar; Khan Chowdhury, Ahmed Jalal (Chelonian Research Foundation, 2018)
The microhabitats of green turtle (Chelonia mydas) nests were investigated to identify key factors influencing nesting success by monitoring both successful nests (n = 43) and aborted nests (n = 106) created by the same individuals (n = 9) from September 2013 to September 2014 on Penang Island, Malaysia. The effect of sand particle size on nesting success was significant, suggesting that green turtles tend to abort nesting at sites with sands of particle sizes < 1 mm. In addition, nests were successful at superficial sand temperatures less than 32.95°C.